Implikasi Makna Sabat bagi Tanah dalam Imamat 25:1-7 bagi Orang Percaya - Sabda Budiman; Enggar Objantoro (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2021)
One of the most important themes in the Old Testament is the Sabbath. In the life of the Israelites, discussion of the Sabbath was not only related to days, but to years. In its application, the Sabbath is not only reserved for humans and animals, it is also applied to the land. The concept of the Sabbath for the land also gave deep meaning to the life of the Israelites, starting from the practical to the main thing. One of the current issues is what are the implications of the meaning of the sabbath for the land for believers today? These questions become the writer's reference in examining more deeply the meaning of the Sabbath for the land in the lives of the Israelites. In the discussion, the author gives an explanation of the meaning of the Sabbath for the Israelites, of course with a focus on God. The method that I use in this article is a qualitative method with a descriptive approach. The author collects various data sources related to the topics discussed and analyzes in order to find a complete and precise understanding. Through this research, it was found that believers have a social responsibility and responsibility in maintaining the environment. Abstrak Salah satu tema penting di dalam Perjanjian Lama ialah tentang sabat. Dalam kehidupan bangsa Israel, pembahasan tentang sabat tidak hanya dikaitkan dengan hari saja, berhubungan dengan tahun. Dalam penerapannya pun sabat tidak hanya diperuntukkan bagi manusia dan hewan, sabat juga diberlakukan bagi tanah. Konsep sabat bagi tanah juga memberikan makna yang mendalam bagi kehidupan bangsa Israel, mulai dari hal yang praktis hingga kepada hal yang pokok. Salah satu persoalan saat ini ialah apakah implikasi makna sabat bagi tanah bagi orang percaya masa kini? Pertanyaan-pertanyaan ini menjadi acuan penulis untuk mengkaji lebih mendalam makna sabat bagi tanah dalam kehidupan umat Israel. Dalam pembahasan, penulis memberikan paparan terhadap makna sabat bagi orang Israel, tentunya dengan berpusat pada Allah. Metode yang penulis gunakan dalam artikel ini ialah metode kualitatif dengan pendekatan deskriptif. Penulis mengumpulkan berbagai sumber data yang berkaitan dengan topik yang dibahas dan menganalisis guna menemukan pengertian yang utuh dan tepat. Melalui penelitian ini, didapati bahwa orang percaya memiliki tanggung jawab social dan tanggung jawab dalam memelihara lingkungan.